The impact of the high level of intensity training process on the performance and recovery of young swimmers at the national level - Gussakov, I.; Nurmukhanbetova, D.; Kulbayev, A.; Yermakhanova, A.; Lesbekova, R.; Potop, V. (Journal of Physical Education and Sport, 2021)
This article describes the effect of the 8-week low-volume training process for high level of performance young swimmers who compete at the national level. Material. In the experiment, fourteen swimmers took a part, they were distributed into two groups. The experimental group had a high-intensity training with low training volume, and the control group was training following traditional methods. The experimental group reduced the amount of weekly training in zone 1 (low intensity zone) by 50%, but increased training in 3 zones (zone of highfrequency) by 200%. The control group did not make changes in the training process. Results. As a result, there was a significant interaction between time and groups in terms of swimming speed at a lactate level of 4 m/mol. Also, the 8-week low-volume training process with a high level of intensity had a significant impact on the performance parameters and psychological state of recovery. Conclusion. The main conclusion of the study was that the eight-week HIT experiment led to an increase in the swimming speed at the level of 2 and 4 m / mol of lactate in the blood of the experimental group. In the control group, these indicators remained almost unchanged.